The Phoenix program and contemporary counterinsurgency - Rosenau, William (Occasional paper (Rand Corporation), 2009)
Counterinsurgency campaigns in Afghanistan and Iraq have reawakened official and analytical interest in the Phoenix Program. But Phoenix remains one of the most misunderstood aspects of the Vietnam War. Some believe it to have been devastatingly effective against the Viet Cong (VC), while others believe it to have been nothing more than an assassination program. This paper seeks to clarify what Phoenix was (and was not) while also attempting to determine what elements of Phoenix remain relevant to contemporary counterinsurgency.